(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
The research aimed to measure the negative impact of monetary shocks on the capital adequacy of the Iraqi banking sector for the period 2004-2022 using the Threshold Regression Model. The results of the research showed that there is an impact of the variables of monetary shocks (money supply, exchange rate, interest rate, index number). (prices) on the (banking sector capital adequacy) index. The most important findings of the research are that the banking sector capital adequacy at the threshold is less than 2.8984929 trillion. There was a positive impact of the money supply shock on the banking sector capital adequacy. However, when capital The banking sector is confined between 7.6688449 and 2.8984929, so the effect of the money supply shock on the capital adequacy of the banking sector is positive. However, in the third system, when the capital threshold is less than 11.73928 and greater than 7.6628449, there was a negative effect for both (the interest rate shock and the supply shock) at a significant level. 5%, while there was a significant positive effect of the exchange rate shock, and in the fourth system at the capital threshold greater than or equal to 11.73928, there was a negative effect of the price index shock at a significant level of 5%, while here there was a significant positive effect for both (the interest rate shock and the money supply).